Reproductive aspects of the mosquito Culex quinquefasciatus (Diptera:Culicidae) infected with Wuchereria bancrofti (Spirurida: Onchocercidae) - Lima Catarina A; Almeida Walkiria R; Hurd Hilary; Albuquerque Cleide MR (Memorias do Instituto Oswaldo Cruz, 2003)
This study reports on the relationship between Wuchereria bancrofti infection and female body size, intake of blood and fecundity in the mosquito Culex quinquefasciatus, vector of this filarial parasite in Recife (Brazil). Adults from field collected larvae were infected via a membrane feeding procedure, using blood with parasitaemia ranging from 724-6,000 mf/ml. A positive correlation was observed between mosquito size (measured by wing length) and egg production in uninfected females. However, this relationship did not exist in W. bancrofti infected mosquitoes. This change is unlikely to be the result of changes in blood ingestion as no significant difference was found when infected and uninfected females were compared. Variation in egg production observed between trials could not be associated with parasite density in the blood. These results suggest infection with W. bancrofti may disrupt the relationship between mosquito size and egg production during the first gonotrophic cycle of C. quinquefasciatus such that fecundity is sometimes reduced. However, this overall affect is variable and many groups of mosquitoes do not respond in this way.